2012
DOI: 10.1007/s00586-012-2401-1
|View full text |Cite
|
Sign up to set email alerts
|

Is pregnancy related pelvic girdle pain associated with altered kinematic, kinetic and motor control of the pelvis? A systematic review

Abstract: Purpose To determine the level of evidence for altered mechanical and motor control of the pelvis being associated with pregnancy-related pelvic girdle pain (PPGP). Methods This systematic review was undertaken by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Six different databases were used for the electronic search. Observational cohorts, cross sectional or case-control studies focused on the association between altered kinematic/kinetic and motor cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 56 publications
0
54
0
5
Order By: Relevance
“…Studies with five or more points were considered as high quality (Aldabe et al. ). A full explanation of the NOS can be found in Appendix S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with five or more points were considered as high quality (Aldabe et al. ). A full explanation of the NOS can be found in Appendix S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that in pelvic girdle pain there is altered mechanical and motor control of the pelvis 19. With regard to the altered mechanics, symphyseal separation of more than 9–13 mm and a change in the shape of the symphysis may play a role in pelvic girdle pain.…”
Section: Musculoskeletal Symptoms In Pregnancy: Low Back Painmentioning
confidence: 99%
“…The two review papers by Aldabe et al [2,3] concerning pelvic pain in pregnancy were intriguing. We learn that it affects 20 % of pregnant woman, and they are three times more likely to get a post-partum depression.…”
Section: R C Mulholland (And)mentioning
confidence: 99%